Haematological studies in pregnant Beetal x Assam local goat - BHATTACHARYYA, H K; GOSWAMI, B K; CHAKRAVARTY, P; BISWAS, R K (The Indian Journal of Animal Reproduction, 2023)
Different haematological constituents were studied in twenty impregnated crossbred (Beetal x Assam~oc~l) goats. The packed cell volume, number of erythrocytes and different leucocytic count did not differs1gnificantly. However, the overall mean values were found to be reduced significantly during early pregnancy forhaemogobin content (P
Keywords: Haematological value; goat; pregnancy